Implementation of Law Number 21 of 2008 Concerning Sharia Banking Against Sharia Financial Institutions - Hidayat, Taufik; Muhammad Majdidin, Rijah; Ridwan Habibi, Yogi; Noviarita, Heni (KnE Social Sciences, 2024)
The role of Law Number 21 of 2008 concerning Islamic Banking for Islamic financial institutions is very large. This is because Islamic financial institutions (LKS) currently have legal certainty to be able to carry out Islamic economic activities in Indonesia. The existence of the Sharia Banking Law provides an answer to the sustainability of the Islamic economy in Indonesia as a whole, including the activities of Islamic financial institutions in the form of banks and non-banks. According to the normative juridical point of view, the legal basis for sharia economic dispute resolution in Indonesia is Law Number 3 of 2006 concerning the Religious Courts and Law Number 4 of 2004 concerning Judicial Power as a form of upholding legal justice for the community in carrying out economic activities. Keywords: financial, banking, Sharia institutions